Reexamination of Chlorophyllase Function Implies Its Involvement in Defense against Chewing Herbivores . Issue 3 (12th January 2015) - Hu, Xueyun; Makita, Satoru; Schelbert, Silvia; Sano, Shinsuke; Ochiai, Masanori; Tsuchiya, Tohru; Hasegawa, Shigeaki F.; Hörtensteiner, Stefan; Tanaka, Ayumi; Tanaka, Ryouichi
Abstract : A jasmonate-inducible chlorophyllase catabolizes chlorophyll upon tissue disruption to generate compounds that are toxic to insect herbivores. Abstract: Chlorophyllase (CLH) is a common plant enzyme that catalyzes the hydrolysis of chlorophyll to form chlorophyllide, a more hydrophilic derivative. For more than a century, the biological role of CLH has been controversial, although this enzyme has been often considered to catalyze chlorophyll catabolism during stress-induced chlorophyll breakdown. In this study, we found that the absence of CLH does not affect chlorophyll breakdown in intact leaf tissue in the absence or the presence of methyl-jasmonate, which is known to enhance stress-induced chlorophyll breakdown. Fractionation of cellular membranes shows that Arabidopsis ( Arabidopsis thaliana ) CLH is located in the endoplasmic reticulum and the tonoplast of intact plant cells. These results indicate that CLH is not involved in endogenous chlorophyll catabolism. Instead, we found that CLH promotes chlorophyllide formation upon disruption of leaf cells, or when it is artificially mistargeted to the chloroplast. These results indicate that CLH is responsible for chlorophyllide formation after the collapse of cells, which led us to hypothesize that chlorophyllide formation might be a process of defense against chewing herbivores. We found that Arabidopsis leaves with genetically enhanced CLH activity exhibit toxicity when fed to Spodoptera litura larvae, an insect herbivore. In addition, purified chlorophyllide partially suppresses the growth of the larvae. Taken together, these results support the presence of a unique binary defense system against insect herbivores involving chlorophyll and CLH. Potential mechanisms of chlorophyllide action for defense are discussed.